PHYLOGENY OF WILD AND CULTIVATED COWPEA (VIGNA UNGUICULATA L. WALP) BASED ON PHENOTYPIC TRAITS AND SSR MARKERS - ogunkanmi, adebayo; ogundipe, oluwatoyin; omoigui, lucky; odessye, adebola; fatokun, christian (Journal of Agricultural Sciences (Belgrade), 2019)
Phylogeny of wild and cultivated cowpea were assessed using morphometric and molecular analyses. Three hundred and ninety accessions comprising 260 cultivated and 130 wild cowpea were evaluated phenotypically using 27 cowpea descriptors. Morphological evaluation of some qualitative characters revealed 11.92% and 29.23% presence of pigmentation on stem, 20.76% and 1.53% presence of stripes on pod, and 0% and 20% presence of hairiness on plant for cultivated and wild cowpea respectively. In the molecular analysis, sixteen SSR primers were employed for genotyping 48 accessions from both wild and cultivated cowpeas. The data generated a dendrogram with three clusters, two of which consisted of wild cowpea while the third cluster comprised of all the cultivated cowpeas, including the yard-long-bean (Vigna unguiculata subsp. sesquipedalis) and Vigna unguiculata subsp. cylindrica accessions. Two wild accessions of subsp. Dekindtiana, and one each of subsp. kgalagadensis and protracta clustered with cultivated cowpea indicating their relationships with cultivated cowpea than other wild cowpea. The number of polymorphic SSR bands in cultivated and wild cowpea were 38 and 54, respectively, while the PIC values were 4.47 and 6.14, respectively, showing a greater genetic diversity in the wild than cultivated cowpea. The subsp. dekindtiana had the highest number (80%) of shared SSR bands with cultivated cowpea followed by subsp. protracta with 54% shared bands. Five species of wild cowpea have hairs and so could be used in breeding for resistance to insects. Results presented here suggest that subsp. dekindtiana and subsp. protracta could be the progenitors of cultivated cowpea.